Effects of instructional approaches, attitude, and gender on financial accounting achievement among secondary school students in Nigeria - Inuwa, Umar (2017)
The financial accounting achievement of secondary school students in Nigeria over the years has persistently remained not encouraging, especially in their national examination. This is due to the persistent use of the conventional teaching approach. Several studies in other subject areas have documented that effective instructional approaches have significantly improved students’ achievement. However, arguments exist in the literature that knowing students’ attitude towards a subject could help the teacher to use appropriate instructional approaches to address the students’ learning problems. Therefore, this study extended the work of previous studies by examining the effects of instructional approaches, attitude, and gender on financial accounting achievement among secondary school students in Nigeria. An explanatory sequential mixed-method design was adopted where a cluster sampling technique was used in the study. The quantitative data were collected from 240 students, while twelve students participated in the interview. The data collected were statistically treated using ANCOVA, multiple regression, and t-test, while NVivo was used in analysing the qualitative data. The results revealed that cooperative instructional approach is the most effective approach for teaching financial accounting to secondary school students compared to the demonstration, guided discovery, and conventional approaches. Students’ attitude towards financial accounting also has a significant influence on their financial accounting achievement, whereas students’ gender difference has no influence on their financial accounting achievement. By implications, the findings of the present study suggest that the government should encourage curriculum planners and financial accounting teachers of secondary schools to adopt the cooperative instructional approach as an instructional approach for teaching financial accounting in secondary schools to improve their students’ achievement in the subject. Furthermore, financial accounting students should be motivated, especially by their teachers to develop a more positive attitude towards financial accounting. This will also help in improving their achievement in the subject.